One‐Step Exfoliation Method for Plasmonic Activation of Large‐Area 2D Crystals. Issue 32 (14th September 2022) - Fu, Qiang; Dai, Jia‐Qi; Huang, Xin‐Yu; Dai, Yun‐Yun; Pan, Yu‐Hao; Yang, Long‐Long; Sun, Zhen‐Yu; Miao, Tai‐Min; Zhou, Meng‐Fan; Zhao, Lin; Zhao, Wei‐Jie; Han, Xu; et al.
Abstract: Advanced exfoliation techniques are crucial for exploring the intrinsic properties and applications of 2D materials. Though the recently discovered Au‐enhanced exfoliation technique provides an effective strategy for the preparation of large‐scale 2D crystals, the high cost of gold hinders this method from being widely adopted in industrial applications. In addition, direct Au contact could significantly quench photoluminescence (PL) emission in 2D semiconductors. It is therefore crucial to find alternative metals that can replace gold to achieve efficient exfoliation of 2D materials. Here, the authors present a one‐step Ag‐assisted method that can efficiently exfoliate many large‐area 2D monolayers, where the yield ratio is comparable to Au‐enhanced exfoliation method. Differing from Au film, however, the surface roughness of as‐prepared Ag films on SiO2 /Si substrate is much higher, which facilitates the generation of surface plasmons resulting from the nanostructures formed on the rough Ag surface. More interestingly, the strong coupling between 2D semiconductor crystals (e.g., MoS2, MoSe2 ) and Ag film leads to a unique PL enhancement that has not been observed in other mechanical exfoliation techniques, which can be mainly attributed to enhanced light‐matter interaction as a result of extended propagation of surface plasmonic polariton (SPP). This work provides a lower‐cost and universal Ag‐assisted exfoliation method, while at the same time offering enhanced SPP‐matter interactions. Abstract : Here, the authors discover a universal Ag‐assisted exfoliation method, which can be used to directly integrate large‐scale 2D crystals with plasmonic nanostructures. The long propagation of surface plasmonic polariton in the hybrid structures results in extraordinarily photoluminescence enhancement for monolayer MoS2 and MoSe2 . This technique allows to direct preparation and exploration of optical properties of emergent 2D crystals, which paves a new way for preparing large‐scale 2D materials and their future applications.